ZeroâEnergy Buildings and Energy Efficiency towards Sustainability: A Bibliometric Review and a Case Study - Manzoor, B. (MDPI, 2022)
The rapid growth of sustainability has created a plethora of options for expanding zero-energy buildings (ZEBs) and energy efficiency in all aspects of life. In recent years, there has been a rise in interest in ZEBs, and many countries have adopted ZEBs as future energy targets to promote the sustainable development paradigm. The primary goal of this paper was to conduct a bibliometric review of current research on ZEBs and energy efficiency. The first part of this paper identifies new knowledge gaps as well as practical demands in the field of sustainable development. Furthermore, bibliometric analysis was performed using the Scopus database (i.e., 2592 articles) and a screening process was undertaken, with the result being 252 papers. This study draws attention to a body of knowledge by reviewing trends and patterns, major research topics, journals, countries, new approaches, emerging trends, and future directions for sustainable development. This study is unique in that it provides a comprehensive, updated review of ZEBs and energy efficiency trends. Moreover, this study could help identify limitations for future policymakers, practitioners, and academics. The empirical section of this paper, through a case study, presents an example of a low-energy singleâfamily building located in Poland. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.